(untitled) (The Pakistan Development Review, 1994)
Ibn Abidin (1784-1836) was the first scholar in the Muslim world to discuss the meaning and legal character of insurance.1 Islamicity of insurance has been under discussion since then. Opinions regarding legitimacy, adoption, and adaptability of insurance are numerous. Recently, however, a consensus was emerging for adapting insurance in the name of takafol and solidarity. As a result, several Islamic takafols and solidarity companies have been established since 1979. During the last decade the Council of Islamic Ideology Pakistan (ClIP) reviewed the operations of the existing takafols in order to find a suitable model for Pakistan.2 While declaring all of them incompatible with the injunctions of Islam, the ClIP proposed its own model of takafol, instead. Its rejection of existing takafols is a little paradoxical since the operations of all the takafols are claimed to be compatible with the Shariah. Each takafol guarantees Shariah compatibility of its operations by sUbjecting itself to the dictates of a Shariah Supervisory Board, which are empowered to review the company’s practices, contracts, transactions and operations. This paper attempts to delineate the points of contact and convergence between insurance and takafol, and to .make recommendations for possible improvement in the takafol concept. The study is organised as follows: Islamic debate on insurance, with special reference to its application to takafols, is reviewed in Section II. Pertinent operational features of takafols are compared with insurance in Section III. The ClIP model is examined in Section IV. The final section features proposals meant to augment the conformity of takafol with the principles of Shariah.